Absolute configuration of polypropionate derivatives: Decempyrones A–J and their MptpA inhibition and anti-inflammatory activities - Guo, Heng; Wu, Qilin; Chen, Dongni; Jiang, Minghua; Chen, Bin; Lu, Yongjun; Li, Jing; Liu, Lan; Chen, Senhua (Bioorganic chemistry, 2021)
[Display omitted] •Ten new polypropionate derivatives, decempyrones A–J (1–10) were isolated from Fusarium graminearum.•Absolute configurations were fixed by JBCA, chemical degradation, geminal proton rule, and modified Mosher’s method.•Decempyrones C and J exhibited potent anti-inflammatory activity.•Decempyrones C and J also displayed MptpA kinase inhibitory activity. Under guidance of 1H NMR, ten new polypropionate derivatives, decempyrones A–J (1–10) along with two known analogues (11 and 12), were isolated from the marine-derived fungusFusarium decemcellulare SYSU-MS6716. The planar structures were elucidated on the basis of extensive spectroscopic analyses (1D and 2D NMR, and HR-ESIMS). The absolute configuration of the chiral centers in the side chain is a major obstacle for the structure identification of natural polypropionate derivatives. Herein, the J-based configurational analysis (JBCA), chemical degradation, geminal proton rule, and the modified Mosher’s method were adopted to fix their absolute configurations in the side chain. Compounds 3 and 10 exhibited potent anti-inflammatory activity by inhibiting the production of NO in RAW264.7 cells activated by lipopolysaccharide with IC50values 22.4 ± 1.8 and 21.7 ± 1.1 μM. In addition, compounds 3 and 10 displayed MptpA inhibitory activity with an IC50 value of 19.2 ± 0.9 and 33.1 ± 2.9 µM. Structure-activity relationships of the polypropionate derivatives were discussed.